Flood Inundation Analysis Using HEC-6 And Arcview GIS 3.2a - Sinnakaudan, Shanker Kumar; Ghani, Aminuddin Ab; Chang, Chun Kiat (2002)
An integration procedure namely AVHEC6.avx has been created between Arc View GIS 3.2a and HEC-6 hydraulic model to perform flood inundation analysis. The procedure was tested using hydraulic and hydrological data for Pari River channel and floodplain with the reach approximately 4 km long.